Correlation between FIX genotype and pharmacokinetics of Nonacog alpha according to a multicentre Italian study. (14th March 2016) - Morfini, M.; Dragani, A.; Paladino, E.; Radossi, P.; Di Minno, G.; Mazzucconi, M. G.; Rossetti, G.; Barillari, G.; Napolitano, M.; Tagariello, G.
Abstract : Introduction: Pharmacokinetic (PK) studies on recombinant FIX concentrate, Nonacog alpha, were conducted with different sampling time designs which gave rise to not complete and homogenous outcomes. In addition, patient's FIX genotype/PK relationship has never been investigated. Aim: Investigate how different sampling times may affect PK parameters and try to find a FIX genotype/PK relationship. Patients and Methods: A cohort pharmacokinetic, Nonacog Alpha single‐dose, open‐label, non‐comparative study was conducted in eight Comprehensive Care Haemophilia Centres in Italy. Seventeen previously treated moderate or severe haemophilia B patients were enrolled. Factors IX:C one‐stage clotting assay, FIX genotype and PK analysis were centralized. Results: The evaluation of PK outcomes showed a quite long half‐life, smaller clearance and volume of distribution of Nonacog Alpha in comparison with the results from previously reported studies, where blood sampling was stopped too early. The relationship between PK outcomes and FIX genotype showed that small deletions displayed the higher clearance and shorter half‐life, the nonsense mutations (the lower and the longer respectively), and missense mutations were in between. Conclusions: It is evident that area under the curve (AUC) and other PK parameters depend from the sampling time design. In order to have a complete evaluation of clotting factors in vivo decay, blood samples must be collected until the baseline factor concentration has been achieved again. Due to the relationship between FIX genotype and clearance, tailored prophylaxis of HB patients could be partially predicted by genotyping.